Environmental Accounting: Analysis of Research Trend By Using Content Mining - Fifitri Ali; Meliza Putriyanti Zifi (Politeknik Caltex Riau, 2021)
The current research leads a substance mining procedure to dissect the articles dependent on bibliographic coupling investigations to decide the remarkable examination subjects. These natural bookkeeping research subjects are confirmed with those intermediaries by the Environmental Management Accounting system with the absolute 71 articles from 2017 to 2020 were dissected. Regarding subjects came about seventeen subjects. The outcome discovered three EMA's point did exclude from CATAR, for example, emission allowances, environmental shareholder value and corporate eco-efficiency. The aftereffects of this study will help researchers investigate their own field strengths, comprehend the creating patterns in environmental accounting research, demonstrate researchers who have had impact in environmental accounting research, and decide future research subjects.